2008
DOI: 10.1002/mrm.21520
|View full text |Cite
|
Sign up to set email alerts
|

Generalized MRI reconstruction including elastic physiological motion and coil sensitivity encoding

Abstract: This article describes a general framework for multiple coil MRI reconstruction in the presence of elastic physiological motion. On the assumption that motion is known or can be predicted, it is shown that the reconstruction problem is equivalent to solving an integral equation-known in the literature as a Fredholm equation of the first kind-with a generalized kernel comprising Fourier and coil sensitivity encoding, modified by physiological motion information. Numerical solutions are found using an iterative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 23 publications
1
61
0
1
Order By: Relevance
“…NMI is a well-known concept that is often used to image coregistration for both intramodality and intermodality images [8][9][10]. Recently, Jiang and colleagues [11,12] introduced the use of NMI as a reference image with which to evaluate image quality. We assumed that the NMI-based technique would work successfully for three-dimensional (3D) volume images.…”
Section: Semiconductor Detectors Have In Recent Times Emerged As a Nementioning
confidence: 99%
See 1 more Smart Citation
“…NMI is a well-known concept that is often used to image coregistration for both intramodality and intermodality images [8][9][10]. Recently, Jiang and colleagues [11,12] introduced the use of NMI as a reference image with which to evaluate image quality. We assumed that the NMI-based technique would work successfully for three-dimensional (3D) volume images.…”
Section: Semiconductor Detectors Have In Recent Times Emerged As a Nementioning
confidence: 99%
“…In addition, it was already demonstrated that NMI values calculated between the reference image and acquired images can be used to evaluate image quality [11,12,20].…”
Section: Use Of Normalized Mutual Informationmentioning
confidence: 99%
“…This work can be extended to multiple coil acquisition (8), by combination with the general parallel imaging method proposed in (9). The resulting framework involves modeling the acquisition pipeline as shown in Fig.…”
Section: Generalized Reconstruction Framework For Arbitrary Motion Comentioning
confidence: 99%
“…This article starts by presenting a reconstruction framework also descibed in (8), generalizing methods in (7) and (9), in order to correct for artifacts caused by elastic motion (nonrigid or affine) in the context of multiple coil acquisition. Practical implementation requires knowledge of complete displacement fields at each acquisition time.…”
Section: Introductionmentioning
confidence: 99%
“…Then in (19), elastic spatial transformation operator T ti was incorporated in the equation of generalized SENSE:…”
Section: Gricsmentioning
confidence: 99%